Phytotoxicity and Accumulation of Copper-Based Nanoparticles in Brassica under Cadmium Stress - Shiqi Wang; Yutong Fu; Shunan Zheng; Yingming Xu; Yuebing Sun (Nanomaterials, 2022)
The widespread use of copper-based nanoparticles expands the possibility that they enter the soil combined with heavy metals, having a toxic effect and posing a threat to the safety of vegetables. In this study, single and combined treatments of 2 mg/L Cd, 20 mg/L Cu NPs and 20 mg/L CuO NPs were added into Hoagland nutrient solution by hydroponics experiments. The experimental results show that copper-based Nanoparticles (NPs) can increase the photosynthetic rate of plants and increase the biomass of Brassica. Cu NPs treatment increased the Superoxide Dismutase (SOD), Peroxidase (POD) and catalase (CAT) activities of Brassica, and both NPs inhibited ascorbate peroxidase (APX) activity. We observed that Cd + Cu NPs exhibited antagonistic effects on Cd accumulation, inhibiting it by 12.6% in leaf and 38.6% in root, while Cd + CuO NPs increased Cd uptake by 73.1% in leaves and 22.5% in roots of Brassica. The Cu content in the shoots was significantly negatively correlated with Cd uptake. The Cd content of each component in plant subcellular is soluble component > cytoplasm > cell wall. Cu NPs + Cd inhibited the uptake of Zn, Ca, Fe, Mg, K and Mn elements, while CuO NPs + Cd promoted the uptake of Mn and Na elements. The results show that copper-based nanoparticles can increase the oxidative damage of plants under cadmium stress and reduce the nutritional value of plants.